THE INFLUENCE OF ONLINE IMPULSE BUYING ON GENERATION Z: A SYSTEMATIC LITERATURE REVIEW APPROACH - Mardiana Mardiana; Ismanto Ismanto; Hanif Kurniadi (Universitas KH. Abdul Chalim Mojokerto, 2026)
The development of e-commerce and social commerce has driven increased online impulse buying behavior, particularly among Generation Z, who have a high level of digital technology usage. This study aims to synthesize empirical findings related to factors influencing online impulse buying behavior among Generation Z through a Systematic Literature Review (SLR) approach. A literature search was conducted on English-language publications published between 2018 and 2025 through the Science Direct, Google Scholar, and ProQuest databases. The selection process followed PRISMA guidelines and resulted in 13 articles meeting the inclusion criteria. The review results indicate that Generation Z's online impulse buying behavior is influenced by various digital stimuli, such as platform quality, scarcity-based promotions, digital figure characteristics, price perception, and shopping lifestyle. These influences are generally mediated by psychological and affective mechanisms, including flow experience, shopping enjoyment, perceived enjoyment, arousal, pleasure, and consumer trust. These findings confirm that Generation Z's impulsive buying decisions are not solely driven by rational considerations, but also by digital experiences and emotional engagement shaped by the online shopping environment. This study provides a conceptual contribution by presenting a structured mapping of the determinants of online impulse buying in Generation Z as well as practical implications for the development of digital marketing strategies based on user experience and sustainable social interactions.